ANALYSIS OF UNILATERAL PRICE STANDARD IN THE PALM OIL TRADING SYSTEM REVIEWED FROM AN ISLAMIC LAW PERSPECTIVE: A case study in South Aceh District, Indonesia - Haryadi; Dedy Sumardi (JURISTA: Jurnal Hukum dan Keadilan, 2025)
Farmers conduct the purchase and sale of palm oil in Gampong Malaka after the harvest is completed by directly contacting their regular agents. Generally, farmers wait for agents to come and buy their harvest, paying directly at the transaction site. However, some agents also visit the farmers' plantations to weigh the harvest. The agent typically makes payment to the farmers after the palm oil is resold to the processing factory, and the price is determined unilaterally by the agent. The method used in this study is the empirical legal method, with informants consisting of agents/tauke and the palm oil farmer community. Data collection was conducted through interviews and documentation. The study's findings indicate that, according to Islamic economic law, there is an element of gharar in the unilateral deduction carried out by the ram. This unilateral deduction has become a custom (urf) for the people of Gampong Malaka because the practice has been carried out for a long time and is deeply ingrained in the community. However, the gharar here falls under the category of minor gharar, which is still permissible or allowed because the community of Gampong Malaka understands and has no issues with it, as it is considered to be within reasonable limits and does not cause any problems that need to be debated regarding unilateral deductions in oil palm transactions.